ORDERING INFORMATION SYSTEMS AND ACCEPTANCE OF GOODS IN PT. EURO STAR GARMINDO USING MICROSOFT ACCESS - Maryanah Maryanah; Fitri Sjafrina, Ir, Skom, MMSI (Jurnal Sistem Informasi, 2002)
PT. Euro Star Garmindo is one of the many companies engaged in the garment. Thecompany needed a fast service in processing data increasing reservations. Constraintsfaced by ole PT was seeking data based on alphabetical order. This is due to still usethe recording in data processing and reporting. To the authors offer an alternativesolution which is expected to help the company.Use a computer with a Microsoft Access application is one way that can be used tofacilitate the officers in making goods stock reports. For storage data using acomputer model of the author of RAM 486 with 8 MB, this is in accordance with thereservation data processed by the company. With the computerization is expected toassist in the ordering of goods production needs.